Kesiapan Belajar Jenjang Sekolah Menengah Atas (SMA) dalam Implementasi Kurikulum Merdeka (IKM) di Kabupaten Nias Utara - Doni Berkat Tabah Hulu; Alianus Zalukhu; Herman Herman; Nesti Surya Astuti Zebua; Dame Ifa Sihombing; Simon M Panjaitan (Journal on Education, 2023)
The background of this research is the Implementation of the Independent Curriculum (IKM) as a result of curriculum changes, it is rumored that the Implementation of the Independent Curriculum (IKM) is less effective, because there has not been maximum preparation in terms of outreach, implementers in the field, as well as teachers, as well as various supporting infrastructure. The implementation of the Independent Curriculum (IKM) is all wrapped up in four indicators of readiness, including: physical condition, mental condition, emotional condition, needs (motivation) and knowledge. Therefore, researchers have the desire to test the level of readiness for the Implementation of the Independent Curriculum (IKM), because schools are required to be oriented towards changing the existing curriculum in order to achieve the ideals of the nation. The research method used was the survey method, with the instrument used, namely a questionnaire, which was distributed to 60 teachers from 13 schools at the high school level (SMA) randomly in North Nias Regency. Based on the results of research on the level of learning readiness at the senior high school (SMA) level in the Implementation of the Independent Curriculum (IKM) in North Nias district, the 4 indicators studied were in the fairly prepared category.